The role of teacher professional development in financial literacy education: A systematic literature review. (February 2019) - Compen, Boukje; De Witte, Kristof; Schelfhout, Wouter
Abstract: This paper examines the elements essential to effective teacher professional development (TPD) in financial literacy education by means of a systematic literature review. We provide a theoretical underpinning for the literature review by proposing a revised presentation of an existing general TPD model. Our results provide insight into the student learning goals in financial literacy education, the desirable teaching behaviour, the required teacher quality and the contextual factors that play a role. However, our findings also suggest a lack of studies that systematically investigate whether and how TPD initiatives enhance the effect of financial education on students' financial literacy. Furthermore, existing literature fails to provide insight in how the six key features of TPD should be implemented to optimize its effectiveness. Highlights: Overview of elements essential to effective TPD in financial literacy education. Revised general TPD model, emphasising the interactivity of the model's components. Demands of financial education teachers are well-established in previous literature. Few studies systematically investigate the effectiveness of financial education TPD. Particularly rare are studies evaluating the implementation of TPD's key features.